2014
DOI: 10.1074/mcp.m114.041194
|View full text |Cite
|
Sign up to set email alerts
|

Proteome–Metabolome Profiling of Ovarian Cancer Ascites Reveals Novel Components Involved in Intercellular Communication

Abstract: aOvarian cancer ascites is a native medium for cancer cells that allows investigation of their secretome in a natural environment. This medium is of interest as a promising source of potential biomarkers, and also as a medium for cell-cell communication. The aim of this study was to elucidate specific features of the malignant ascites metabolome and proteome. In order to omit components of the systemic response to ascites formation, we compared malignant ascites with cirrhosis ascites. Metabolome analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 43 publications
5
99
0
2
Order By: Relevance
“…As such, a couple of our top candidates were also discovered in previous proteomic analyses of ovarian cancer ascites fluid (26 -29), including FN1 and SERPIND1. Although, CLCA1 was not found in these fluids, several chloride channelrelated proteins, such as chloride intracellular channel protein (CLIC) 1, CLIC4, and CLIC5, were detected (27)(28)(29). These observations suggest that these proteins may have important roles in cancer progression.…”
Section: Discussionmentioning
confidence: 80%
“…As such, a couple of our top candidates were also discovered in previous proteomic analyses of ovarian cancer ascites fluid (26 -29), including FN1 and SERPIND1. Although, CLCA1 was not found in these fluids, several chloride channelrelated proteins, such as chloride intracellular channel protein (CLIC) 1, CLIC4, and CLIC5, were detected (27)(28)(29). These observations suggest that these proteins may have important roles in cancer progression.…”
Section: Discussionmentioning
confidence: 80%
“…Given the hypoxic microenvironment of ascites in ovarian cancer, exosomes released from tumor cells in ascites carry oncogenic proteins that can alter the signaling pathways in the surrounding recipient tumor cells or normal cells, favoring tumor progression and metastasis 24, 30, 31, 32 . We have shown that activated STAT3, FAS, and other oncogenic proteins were detected in HEx and patient-derived ascites.…”
Section: Discussionmentioning
confidence: 99%
“…FAK phosphorylates β-catenin, which destabilizes the cell-cell junctions, resulting in increased vascular permeability [64]. Metabolome proiling of ascites has revealed signiicant diferences in faty acids, cholesterol, ceramide, glycerol-3-phosphate, glucose and glucose-3-phosphate compared to non-cancerous peritoneal efusions [65]. Whether these changes directly contribute to oncogenic signaling or they merely relect upregulation of pathways of the faty acid synthesis associated with increased metabolic activity in tumor cells remains to be determined.…”
Section: Cell-free Ascites: Biomarkers and Eoc Progressionmentioning
confidence: 99%